Conversational characteristics of children with semantic-pragmatic disorder. II: What features lead to a judgement of inappropriacy? - Bishop, D; Adams, C (1989)
Independent raters scanned transcribed conversations from 57 language-impaired children and 67 control children aged from 4 to 12 years and identified instances where the normal flow of conversation appeared to be disrupted because the child's utterance was in some way inappropriate. It was found that adequate inter-rater reliability could be obtained using this procedure. Furthermore, test-retest correlations for inappropriacy were significant, indicating that this is a stable conversational characteristic. The measure of inappropriacy decreased with age in control children, and it distinguished language-impaired from control children. Those identified as having 'semantic-pragmatic disorder' obtained particularly high scores. In a subsidiary analysis, inappropriate responses were subcategorised. A wide range of semantic, syntactic and pragmatic peculiarities was identified as leading to a sense of inappropriacy. Some instances of inappropriacy appeared to indicate cognitive rather than linguistic difficulties. Children with semantic-pragmatic disorder resembled younger normal children in that they frequently misunderstood the literal or implicit meaning of adult utterances and they violated normal rules of exchange structure. In other respects, however, the semantic-pragmatic group did not resemble normally developing children of any age. In particular, they tended to provide the listener with too much or too little information.